Comorbidities of Chronic Obstructive Pulmonary Disease Patients at Respirology and Critical Care Outpatient Clinic Dr. Hasan Sadikin General Hospital, Bandung, Indonesia - Suhendro, Adrian Sebastian; Santoso, Prayudi; Riswari, Silvita Fitri (Althea Medical Journal, 2017)
Background: Chronic obstructive pulmonary disease (COPD) is a chronic disease that becomes one of the leading causes of death in the world. The COPD is usually accompanied by comorbidities that impact prognosis and increase patientsâ expenses. However, the comorbidities of COPD patients have not yet to be known in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia. This study was aimed to determine the frequency, type and number of comorbidities accompanying COPD.Methods: This study was a retrospective, cross-sectional study at the respirology and critical care outpatient clinic of Dr. Hasan Sadikin General Hospital, Bandung, Indonesia in 2012. Data were obtained from medical records of patients diagnosed with COPD and had an obstructive pulmonary function test result. Sampling technique in this study was total sampling. Data were classified by age, gender, smoking history and severity of disease and were analyzed to determine the frequency, type and number of comorbidities accompanying COPD. Results: Thirty eight COPD patients with obstructive pulmonary function test results were analyzed. It consists of 31 males and 7 females with age ranged between 43â82 years and median age of 64 years. Severe obstruction was found in 15 of 38 patients. Comorbidities were found in 26 patients, and 2 patients had up to four comorbidities. The most common comorbidity was hypertension (9 of 38).Conclusions: The majority of COPD patients had comorbidities and the most frequent comorbidity was hypertension. [AMJ. 2017;4(1):30â5]DOI:Â 10.15850/amj.v4n1.1016